Legislação de compras e desempenho em instituições pública de pesquisa: um estudo de caso na Embrapa Semiárido - Menezes, Luis Magno Silva de (2012)
The purpose of this research was to identify the perceptions of employees about the relationship between the shopping legislation with Embrapa Semia-Arido performance based on efficiency criteria after the implementation of the ´´Pregão´´ proclamation as a new bidding modality. It were developed bibliographical, documental, field, and to ensure the validity of the information we used a triangulation of data collection techniques of document analysis, direct observation and open-ended interviews, held with employees who work or worked in the Sector Purchasing for more than 10 years and they were ´´pregoeiros´´, and researchers from the Unit, also with over 10 years experience, who had approved projects budget with the National Treasure, with performance in previous periods and after the deployment of the ´´Pregão´´. According to the analyzed documentation and from the perspective of the employees of the sector, it was identified that after the implementation of the ´´Pregão´´; the unit has achieved savings possible of resources in hiring an average of 20% below of the baseline established in the notices documents, which could indicate efficiency. However, it became evident that the error rate in the process became much larger in relation to the proceedings conducted before the ´´pregão´´, and that although this modality is indicated as beneficial, there is the impression that is being widely used inappropriately for any hiring without an analysis of bidding modality most appropriate. In this same lineage, with regard to research reports and the opinion of the researchers, it was evident that there has been budget loss for non-delivery processes made in the end of the year, resulting in not meeting goals, steps or tasks of the experiments as well, many delays in the deliveries, and waste of resources due to poor quality acquisitions that are not useful for the research work. Finally, by way of contribution, this study showed that the current public procurement legislation directly influences the performance of Embrapa Semi-Arido, and does not meet your needs as a research institution, indicating that the institution cannot follow the same rules, standards and processes legislation of acquisitions of other public administration institutions, and it needs a new legal apparatus, which gives you more flexibility to run their projects and fulfill its institutional mission